Opioid-Sparing Effects of Flurbiprofen Axetil as an Adjuvant to Ropivacaine in Pre-Emptive Scalp Infiltration for Post-Craniotomy Pain: Study Protocol for a Multicenter, Randomized Controlled Trial - Zhang, Wei; Li, Chunzhao; Zhao, Chunmei; Ji, Nan; Luo, Fang (Journal of pain research, 2023)
Pain after craniotomy remains a poorly controlled problem that is mainly caused by the inflammatory reaction at the incision site. Nowadays, systemic opioids use, as first-line analgesics, is often limited because of adverse effects. Flurbiprofen axetil (FA) is a non-steroidal anti-inflammatory drug merged into emulsified lipid microspheres, which represent a strong affinity to inflammatory lesions. Local administration of flurbiprofen into a surgical wound has induced enhanced analgesic efficacy and few systemic or local adverse effects after oral surgery. However, the impact of local FA, as a non-opioid pharmacologic alternative, remains elusive on postoperative pain in craniotomy. In this study, we presume that pre-emptive infiltration of scalp with FA as an adjuvant to ropivacaine can lead to less sufentanil consumption postoperatively in patient controlled intravenous analgesia (PCIA) compared with ropivacaine alone. We design a multicenter, randomized controlled study that will enroll 216 subjects who are planned to receive supratentorial craniotomy. Patients will receive pre-emptive infiltration of scalp either with 50 mg FA and 0.5% ropivacaine, or with 0.5% ropivacaine alone. Primary outcome is total consumption of sufentanil with PCIA device at 48 h postoperatively. This is the first study attempting to explore the analgesic and safety profile of local FA as an adjuvant to ropivacaine for incisional pain in patients undergoing craniotomy. It will provide additional insights into the opioid-sparing analgesia pathways by local administration of NSAIDs for neurosurgery.